Legal Certainty of Creditors in Land Mortgage Splitting under Law No. 4 of 1996: Kepastian Hukum Kreditur dalam Pembagian Hipotek Tanah berdasarkan Undang-Undang Nomor 4 Tahun 1996 - Widodo, Ilyas; Purwaningsih, Sri Budi (Indonesian Journal of Law and Economics Review, 2025)
Background: Economic growth drives an increasing demand for credit, with land as the most strategic collateral due to its stable value and legal clarity. Specific Background: The split of mortgaged land (splitzing) raises legal concerns regarding the creditor’s rights and the continuation of mortgage obligations. Gap: Limited discussion exists on how mortgage splitting affects creditors’ protection under Indonesian mortgage law. Aim: This study analyzes the implementation of creditor protection in land mortgage splitting based on Law No. 4 of 1996 on Mortgage Rights. Results: The study finds that mortgage splitting must be explicitly agreed upon in the Deed of Mortgage Granting (APHT) and approved in writing by the creditor. Roya (deletion) of mortgage registration occurs only after full repayment. Novelty: This paper highlights the creditor’s legal certainty amidst property division practices. Implications: The findings contribute to strengthening legal frameworks ensuring creditor protection in Indonesia’s mortgage system. Highlights:• Legal certainty of creditors in land mortgage splitting• The necessity of creditor consent in mortgage division• Legal procedure and implications of roya process Keywords: Mortgage, Splitzing, Creditors, Legal Protection, Land Rights